2006
DOI: 10.1200/jco.2006.24.18_suppl.13134
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 study of daily oral perifosine (P) with every 3-week paclitaxel (T)

Abstract: 13134 Background: Perifosine is a novel alkylphospholipid that has been shown to affect multiple signal transduction pathways including Akt, MAPK and JNK (Kondapaka, Mol. Canc. Ther 2: 1093–1103. 2003). Treatment with a taxane initially activates Akt, and persistent activation increases resistance to the drug (Vanderweele, Mol. Canc. Ther. 3: 1605–13, 2004). Methods: Twelve patients (pts) were enrolled on this study. T was given at a dose of 175 mg/m2 on day 8 (after 7 days of perifosine) of a 21 day cycle; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A phase I trial combining perifosine and radiotherapy in advanced solid tumors demonstrated that perifosine could be safely utilized as a radiation sensitizer, and phase II trials with this strategy are in development (Vink et al, 2006b). In addition, preliminary reports from a number of phase I trials investigating the combination of perifosine with traditional cytotoxic chemotherapeutic agents such as taxanes and gemcitabine indicate that these combinations can be safely administered (Cervera et al, 2006;Ebrahimi et al, 2006;Goggins et al, 2006;Weiss et al, 2006).…”
Section: Akt Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase I trial combining perifosine and radiotherapy in advanced solid tumors demonstrated that perifosine could be safely utilized as a radiation sensitizer, and phase II trials with this strategy are in development (Vink et al, 2006b). In addition, preliminary reports from a number of phase I trials investigating the combination of perifosine with traditional cytotoxic chemotherapeutic agents such as taxanes and gemcitabine indicate that these combinations can be safely administered (Cervera et al, 2006;Ebrahimi et al, 2006;Goggins et al, 2006;Weiss et al, 2006).…”
Section: Akt Inhibitorsmentioning
confidence: 99%
“…In trials combining mTOR inhibitors with conventional chemotherapy, unexpected toxicities in two trials lead to early discontinuation of the studies (Punt et al, 2003;Pacey et al, 2004). However, overlapping toxicities were not observed in preliminary data from trials combining perifosine with conventional chemotherapy (Cervera et al, 2006;Ebrahimi et al, 2006;Goggins et al, 2006;Weiss et al, 2006). Nevertheless, combining pathway inhibitors with conventional cytotoxic chemotherapy could result in more toxicity than when combining inhibitors with molecularly targeted agents.…”
Section: Toxicity Concernsmentioning
confidence: 99%
“…In the second trial (NCT00431054)[ 173 ] the safety and efficacy of the combination of docetaxel and perifosine were studied on 22 patients with epithelial cancer of the ovary, fallopian tube cancer or gynecologic primary peritoneal cancer, which were platinum resistant or refractory. The third phase I trial (NCT00399126)[ 174 ] studied the gastrointestinal toxicity and cancer progression on the combination of daily perifosine with weekly or every 3-wk paclitaxel in 12 cancer patients. The preliminary results showed that the combination was well tolerated without increasing the toxicities being expected from using each drug alone.…”
Section: Pi3k/akt Inhibitors In the Clinicmentioning
confidence: 99%
“…The PI3K/AKT pathway mediates major survival signals that protect cells from undergoing apoptosis. Thus, it is possible that in primary CRC conventional cytotoxic chemotherapeutic agents could induce PI3K/AKT activity in cancer cells [Goggins et al 2006], which could confer chemoresistance [Huang and Hung, 2009]. Thus, inhibiting PI3K signaling has the potential to improve the sensitivity of CRCs to the cytotoxic effects of standard chemotherapy.…”
Section: Regimen Design: Rational Combination Therapymentioning
confidence: 99%